2019
DOI: 10.1007/s00296-019-04438-x
|View full text |Cite
|
Sign up to set email alerts
|

The relation between upper extremity joint involvement and grip force in early rheumatoid arthritis: a retrospective study

Abstract: To investigate the relation between joint involvement in the upper extremities and grip force in patients with early rheumatoid arthritis (RA). An inception cohort of 225 patients with early RA was followed according to a structured protocol. The same rheumatologist assessed all patients for swollen joints and joint tenderness. Grip force was measured (Grippit; AB Detektor, Gothenburg, Sweden) at the same visit. Average grip force values for the dominant hand were expressed as % of expected, based on age-and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 48 publications
0
4
0
1
Order By: Relevance
“…Together with shoulders and elbows, wrist joints accounted for the greatest contributions to disease activity, HAQ-DI and long term functional prognosis (41). Several other studies demonstrated a major impact of wrist involvement on grip force in RA (19,22,(43)(44)(45).…”
Section: Discussionmentioning
confidence: 95%
“…Together with shoulders and elbows, wrist joints accounted for the greatest contributions to disease activity, HAQ-DI and long term functional prognosis (41). Several other studies demonstrated a major impact of wrist involvement on grip force in RA (19,22,(43)(44)(45).…”
Section: Discussionmentioning
confidence: 95%
“…In the main analysis, synovitis and joint tenderness of individual joints in both hands were combined. As wrist synovitis, high ESR, and severe patient-reported pain (measured by VAS) were independently associated with reduced grip force in a previous study of this patient sample [ 27 ], and as we were interested in assessing the contribution of individual joints to impaired grip, the main analyses were adjusted for these covariates. By adjusting for ESR and pain, we corrected for potential confounding by general effects of inflammation on strength and impaired performance due to fear of pain.…”
Section: Methodsmentioning
confidence: 99%
“…Information on the contribution of individual joints to impaired grip strength may be helpful for guiding individualized management. We have previously reported that wrist synovitis and extensive metacarpophalangeal (MCP) joint synovitis are associated with reduced grip force in early RA, but the impact of individual finger joints has not been assessed [ 27 ]. The objective of this study was to investigate the relation between swelling and tenderness of individual finger joints and grip force in patients with early RA.…”
Section: Introductionmentioning
confidence: 99%
“…1 Rheumatoid arthritis affecting the MCP joint often results in weakness, instability, pain, and deformity. 1,2 Surgical and nonsurgical techniques are used by physicians and therapists to treat pain and inflammation associated with this condition. 3 Surgery is indicated when less invasive techniques fail to prevent the progression of the patient’s pain and deformity.…”
Section: Introductionmentioning
confidence: 99%